Electoral Reform and Political Representation in Albania: A Comparative Analysis of the 2017, 2021, and 2025 Parliamentary Elections - Xhaferi, Saniela (European Scientific Journal, ESJ, 2026)
This paper examines the effects of recent electoral system reforms on political representation in Albania, with particular attention to vote-seat proportionality, candidate selection mechanisms, gender representation, and regional outcomes. The study adopts a comparative mixed-methods research design, combining quantitative analysis of official election results with qualitative institutional analysis across three parliamentary election cycles (2017, 2021, and 2025), each conducted under different electoral rules. Using a longitudinal case-study approach, the research evaluates how changes in list structures, preferential voting, and gender quotas have reshaped patterns of representation. The empirical findings show that while electoral reforms have expanded voter choice and contributed to a gradual increase in women’s parliamentary representation, their impact on overall democratic representation remains uneven. In particular, the analysis reveals that vote–seat proportionality varies significantly across regions and election cycles, producing disparities that are not fully explained by voter preferences alone. Furthermore, the introduction of preferential voting and modified list structures has not consistently strengthened voter influence over candidate selection, often reinforcing party-level control rather than enhancing electoral accountability. These results suggest that successive electoral reforms in Albania have increased system complexity without delivering proportional improvements in transparency or representativeness. The paper concludes that institutional design alone is insufficient to improve democratic outcomes unless accompanied by broader reforms addressing party practices and governance culture. The findings contribute to ongoing debates on electoral engineering in transitional democracies and offer policy-relevant insights for future electoral reform processes.